(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
In this article, according to a given sequence of eigenvalues , with an accuracy of , the solution of the inverse problem for the Sturm-Liouville operator with an accuracy of is found. The issue of constructing an effective calculation algorithm is discussed.